The development of an Enzyme Linked Immunosorbent Assay for detecting Injectious laryngotrachitis viral antibodies in chicken serum - Indriani, Risa; Adjid, R.M Abdul; ., Darminto; Hamid, Helmy (Indonesian Animal Sciences Society, 2002)
The aim of this study was to develop an Enzyme-linked immunosorbent assay (ELISA) for detection of antibody against gallid herpes virus, the causal agent of infectious laryngotracheitis (ILT) in chicken. Its application in experimental chicken under laboratory condition was also evaluated. Results showed that ELISA for ILT was developed successfully with sensitivity and specificity was 98% and 97,14% respectively. The ELISA was able to determine the dynamic of antibodies respond in experimental chickens following vaccination and artificial infection with ILT virus. It was concluded that this ELISA offers a simple, sensitive and specific antibody assay for detection of antibodies against ILT virus in chickens arising from vaccination or infection. Â Key words: ELISA, antibody, chicken, Infectious laryngotrachitis